PROFESSOR JOSÉ FÉLIX DE RESTREPO EDUCATOR OF COLOMBIA´S INDEPENDENCE GENERATION - Ocampo López, Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This research work is a study on the life and the educational thoughts of Dr. José Félix of Restrepo, the Teacher of the generation of the independence of Colombia who from Popayan, Antioquia and Bogota formed a great many politicians of the first Grenadian Republic and Great Colombia (Gran Colombia). His educational philosophy and his ideas about primary, secondary and university educations were the structural bases that organised and strengthened education in Colombia. Similarly, we emphasize his relentless struggle for the enfranchisement of the slaves.